Who decides whether two lacewing populations (Neuroptera, Chrysopidae) are two different species, them or us? - Duelli, Peter; Koch, Bärbel; Henry, Charles S. (Zootaxa, 2024)
Most insects were dead when they were named by taxonomists, and predominantly morphological criteria have been used for more than two centuries. But in nature there are populations with individuals looking identical, that turn out to represent two or more different species, and others that look different but are single biological species. Coastal and several continental populations of the green lacewing Chrysoperla mediterranea (Hölzel 1972) had been considered to be one species, based on identical precopulatory “song patterns” (Henry et al. 1999) and viable hybrid production. More than 20 years later, Canard & Thierry (2020) described Chrysoperla europaea Canard and Thierry, 2020 as a new species, based on continental specimens, which they decided were morphologically different enough from the coastal morph of C. mediterranea. Here, we test in free choice experiments whether virgin males and females of coastal and continental populations can detect a difference between sexual partners of their own population versus members of the other morph. No reproductive separation between three populations were found, although they show significant morphological differences in claw shape and size. We conclude that all three tested populations from Southern France, Southern Switzerland, and Central Switzerland are the same biological species, and that C. europaea is therefore a junior synonym of C. mediterranea. We suggest the future use of behavioral tests in closely related allopatric species to see whether they are in fact the same species.